Icebound - Koontz, Dean R. (Dean Ray), 1945- (Bantam Books, 2012)
"A tidal wave breaks loose the ice under which a team of scientists has planted sixty powerful explosive charges that will detonate at midnight, and one of the team is an assassin with a mission of his own"--Jacket.